Psychometric Properties of the Environmental Reward Observation Scale: Study on Its Internal Structure, Factor Invariance, and Method Effect Associated With Its Negative Items - Vilca, Lindsey W. (2020)
ABSTRACT The aim of this study was to assess the factorial structure of the scale, the method's effect associated with its negative items, its temporal invariance, and factorial invariance according to sex. For this purpose, three samples were collected, an initial sample of 200 participants, a second sample of 461 participants and a third sample of 107 participants; making a total of 768 Peruvian university students. Other instruments were applied together with the EROS scale in order to measure satisfaction with life, anxiety, stress and depression. Regarding the results, in the initial sample it was found that the original scale containing positive and negative items does adequately fit the data (RMSEA = .19; CFI = .77; TLI = .71) and also evidence was found supporting the existence of a methodological effect associated with the negative items. It was also found that version B of the scale which only has positive items data fits the data (RMSEA = .13; CFI = .96; TLI = .95). In the second sample it was found that version B still had a good fit to the data in a larger sample (RMSEA = .07; CFI = .98; TLI = .98). In addition, it was found that the scale can be considered invariant according to sex and presents validity based on other constructs. In the third sample it was found that the test-retest reliability of the scale was adequate (.70 [CI95% .593–.788]) and also evidence was found in favor of the temporal invariance of the scale. It is concluded that the scale formed only by positive items presents more robust psychometric properties and constitutes a better alternative to measure the level of reward provided by the environment.